Beta-Glucosidase 1 (bgl1) Gene Analysis in Mutant and Wild-type of Penicillium sp. ID10-T065 - Syafriana, Vilya; Nuswantara, Sukma; Mangunwardoyo, Wibowo; Lisdiyanti, Puspita (Jurnal Riset Biologi dan Aplikasinya, 2022)
In the previous study, Penicillium sp. ID10-T065 has been mutated using ultraviolet (UV), ethyl methyl sulfonate (EMS) and the combination of UV-EMS to increase Beta-glucosidase (bgl) activity. There were three mutants selected, UV13 (UV mutant), EM31 (EMS mutant), and UM23 (UV-EMS mutant). This study examined the mutations in the bgl gene encoding (bgl1) as well as sequence differences between mutants and wild-type of Penicillium sp. ID10-T065. The gene analysis was performed by PCR amplification and sequencing of the bgl1 gene. The results of bgl1 gene sequences (600 bp) from mutants were aligned with the wild-type, it was discovered that there were base alterations from position 2025 to 2050. Mutant UV13 showed the highest base alterations (7 bases) which occurred at position 2027 (T?C); 2036 (T?G); 2040 (T?G); 2047 (G?C); and 2048-2050 (TTG?GGA). Mutant EM31 showed alterations in five bases at positions 2034 (G?A), 2036 (T?G), 2037 (G?C), 2044 (G?C), and 2047 (G?T). Mutant UM23 showed two base alterations at position 2025 (T?A) and 2037 (G?C). UV irradiation and EMS mutation resulted in transition and transversion DNA, whereas the combination of UV-EMS mutation resulted in transversion mutations. Base alterations in UV13 and EM31 mutants, causing missense and silent mutation, while in UM23 mutant only silent mutations occur. The bgl1 gene analysis showed that mutation using UV light was more effective than using EMS or a combination of UV-EMS in Penicillium sp. ID10-T065.